(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
Through this research, the aim is to conduct an analysis of the profile and entrepreneurial capacities of undergraduate students at the ECACEN school of UNAD. Based on the results obtained, strategies will be formulated to enable the development and strengthening of students’ entrepreneurial mindset and competencies. These actions aim to encourage students to engage in entrepreneurship as a viable option for generating sustainable income and improving their quality of life. This study corresponds to an exploratory descriptive research, where collected data are measured to then systematically describe, analyze, and interpret the qualities and characteristics of the entrepreneurial profile of ECACEN students at UNAD, based on information obtained from literature review. It is cross-sectional in nature, as the instrument is applied at a single point in time. In conclusion, it is established that a high percentage of undergraduate students at ECACEN in UNAD possess the fundamental qualities to be entrepreneurs. Additionally, these student populations with diverse potentials require entrepreneurial training programs focused on strengthening mindset and entrepreneurial characteristics.